(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In February and March 2017, I conducted a survey among 3 population groups and 392 participants on the state of the population monitoring and disclosure systems so that the information received was up to date. The resulting and aggregated information should not be considered as a constant because the situation changes dynamically, both in terms of the political situation in the region and the intentions of our neighbours regarding the sites that represent both the radiation risk and the meteorological elements that affect any radioactive contamination. Especially dynamic is the development of meteorological elements, which should be analyzed very thoroughly in the event of a nuclear accident or incident. The results of the study are presented, diagrams and analyzes and guidelines for follow-up are presented.